"Maritime Silk Road" Freight Rate Index Forecast Based on ARIMA Model - Wanchao Wang, Guanlin Li, Jiaxing Shi, Liang Chen, Shizhong Shan, Liqun Wang (Forest Chemicals Review, 2022)
Regressive Integrated Moving Average (ARIMA) model was used to accurately understand the changes of shipping prices from China to the Beltand Road countries. Taking the time series of China's "maritime silk road" freight rate index from January 2018 to September 2021 as the training set, the R4.1.2 software was used to carry out the stability analysis, and the ARIMA (0,2,1) model was selected according to the minimum BIC criterion. The mean relative error of forecastwas -12.63, and the absolute error was -5.04%. The model is applied to the price forecast from October to November 2021, and the result shows that the forecastresult of the model is accurate. The ARIMA (0,2,1) model constructed in this paper can provide effective help for China's "the Beltand Road" foreign trade enterprises to timely grasp the law of shipping price changes and make effective decisions.